2015
DOI: 10.1039/c5ra05074j
|View full text |Cite
|
Sign up to set email alerts
|

A simple growth method for Nb2O5 films and their optical properties

Abstract: Synthesis of Nb2O5 thin films from sputter deposited Nb films and its optical property.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 47 publications
2
8
0
Order By: Relevance
“…The Raman analysis results indicated that FeP molecules were successfully deposited on the Au substrates. All vibrational modes were consistent within approximately 10 cm –1 to assignments reported in the literature. , AFM characterization of the bare Au substrate and the FeP self-assembled samples revealed a surface modification that supports the deposition of FeP on the Au substrate. See the Supporting Information for the analysis of the Raman spectra and AFM characterization of the images and surface morphology from FeP.…”
Section: Experimental Methodssupporting
confidence: 85%
“…The Raman analysis results indicated that FeP molecules were successfully deposited on the Au substrates. All vibrational modes were consistent within approximately 10 cm –1 to assignments reported in the literature. , AFM characterization of the bare Au substrate and the FeP self-assembled samples revealed a surface modification that supports the deposition of FeP on the Au substrate. See the Supporting Information for the analysis of the Raman spectra and AFM characterization of the images and surface morphology from FeP.…”
Section: Experimental Methodssupporting
confidence: 85%
“…Deconvolution of the peaks related to the dopants (Nb 3d and Ti 2p) yielded a single doublet for either material. Binding energies for the Nb 3d 5/2 and Ti 2p 3/2 components were 207.6 and 459.2 eV and were assigned to the fully oxidated states (Nb V and Ti IV ) [36,37]. Of note is that the amount of W V species differs from material to material.…”
Section: Resultsmentioning
confidence: 99%
“…10,11 . Niobium element characterized by several valence states from +2 to +4 to +5 for NbO, NbO2 and Nb2O5, respectively 12 , exists in various oxides polymorphic forms including monoclinic (H-Nb2O5), tetragonal (M-Nb2O5), orthorhombic (T-Nb2O5), and pseudo hexagonal (TT-Nb2O5). The different crystal phases of Nb2O5 depend on the synthesis temperature.…”
Section: Imentioning
confidence: 99%
“…7,8 Since the discovery of electrochromism in Nb 2 O 5 in 1980, by Reichman and Bard, 9 niobium oxide has been studied extensively and has come up as a promising electrochromic material because of its chemical stability in many electrolytes, nice reversible color switching, and long-term cycling stability. 10,11 The niobium element characterized by several valence states from +2 to +4 to +5 for NbO, NbO 2 , and Nb 2 O 5 , respectively, 12 exists in various oxide polymorphic forms including monoclinic (H-Nb 2 O 5 ), tetragonal (M-Nb 2 O 5 ), orthorhombic (T-Nb 2 O 5 ), and pseudohexagonal (TT-Nb 2 O 5 ). The different crystal phases of Nb 2 O 5 depend on the synthesis temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation